Brandrisker och skyddshöjande brandtekniska åtgärder för kabelutrymmen inom vattenkraftverk - Johansson, Jonas (2014)
A fire in important cable tunnels inside power plants would lead to stoppage in production that could lead to big financial losses for the owners of the plant, which makes short restoration time very important. With the consequences of stoppage in mind, more focus has been directed to issues regarding fire protection of cable tunnels in the power plants.The purpose of this report is to provide a more comprehensive material to the ongoing investigations within Vattenfall Vattenkraft AB regarding fire protection within their power plants. It will also be used as material for future issues regarding insurance and new projects within Vattenfall Vattenkraft AB.The room that will serve as typical case for this investigation is a cable tunnel inside Harsprånget power plant. The cable tunnel is initially situated approximately 80 meters below ground level in direct connection with the power plant and contains 2-7 cable trays with a varied amount of cables on each tray. The cable tunnel then runs all the way up to ground level.One problem is that the cable tunnel system is more or less open through its whole geometry, which in case of fire in the lower regions could make the whole tunnel system filled with smoke. When adding the fact that the plant is unmanned for the most part, and it’s calculated to take at least 40 minutes before personnel has arrived at the scene in case of fire or other accident. All this makes a fully developed fire very hard to handle. Calculations have been made regarding fire load and maximum heat release rate, and it has been stated that the cable tunnel has a high fire load from the many cable trays, which make oxygen the limiting factor. The cable tunnels closed space and the fact that it´s made of stone and concrete makes the inflow of oxygen very limited. The narrow, complicated geometry is expected to make it impossible for the fire to use all oxygen in the further regions of the tunnel system. This was later verified by simulations made with Fire Dynamics Simulator (FDS).Different ...